Post-mortem analysis of injuries by incomplete hanging in dog (Canis familiaris) through radiographs and forensic necropsy - Gil Mazzante, Nayara Maria [UNESP]; Duarte Ferraz de Camargo, Barbara Wagner [UNESP]; Sanctis, Paula de [UNESP]; Fogaca, Jessica Leite [UNESP]; Vettorato, Michel de Campos [UNESP]; Tremori, Talia Missen; Babboni, Selene Daniela; Vasconcelos Machado, Vania Maria de [UNESP]; Rocha, Noeme Sousa [UNESP] (Elsevier B.V., 2020)
A hanging happens when there is a constriction of the neck caused by a rope pulled by the weight of the victim's body, and it is possible for the victim to die even when it remains on the ground, in what is called an incomplete hanging. In this case report, nine dogs were the subject of an in loco investigation, all of which allegedly victims of abandonment, mistreatment and abuse followed by an accidental hanging that resulted in the death of one of the animals. National and international studies recognize that, when possible, the necropsy should be conducted in association with an x-ray examination whenever possible in cases of violent death and other situations of forensic purview. This case report aims at presenting the radiographic examination as an alternative or complementary method to the necroscopic examination for the diagnosis of incomplete hanging as the causa mortis of a dog (Canis lupus familiaris). The exams revealed a fracture of the hyoid bone and that the causa mortis of the animal was mechanical asphyxia caused by the constriction of the neck by the rope (hanging).
Keywords: Forensic veterinary medicine; Legal medicine; Gross pathology; Animal crime; Forensic Radiology; Abuse